Platelet-rich plasma versus combined fractional carbon dioxide laser with platelet-rich plasma in the treatment of vitiligo: a comparative study - Kadry M; Tawfik A; Abdallah N; Badawi A; Shokeir H (Dove Medical Press, 2018)
Mostafa Kadry,1 Abeer Tawfik,2 Noha Abdallah,2 Ashraf Badawi,2,3 Hisham Shokeir2 1Faculty of Medicine, Dermatology Department, Helwan University Cairo, Helwan, Egypt; 2Dermatology Unit, Department of Medical Applications of Lasers (MAL), National Institute of Laser Enhanced Sciences, Cairo University, Giza, Egypt; 3Department of Allergology and Dermatology, Szeged University, Hungary Purpose: The aim of this study was to assess the efficacy of platelet-rich plasma (PRP) vs combined fractional CO2 (Fr: CO2) laser with PRP in the treatment of stable nonsegmental vitiligo (NSV) lesions. Patients and methods: This prospective, randomized, intrapatient, comparative controlled study was conducted between June 2014 and June 2016 at National Institute of Laser Enhanced Sciences (NILES), Cairo University, Cairo, Egypt. Thirty NSV patients were treated with PRP, Fr: CO2 laser, and combined Fr: CO2 laser with PRP. Intrapatient lesions were divide randomly into four groups. Each group was treated by one modality. The fourth group served as a control. Patients received six treatment sessions with 2-week interval for 3 months and were followed up after 3 months. Results: A highly significant reduction was demonstrated through vitiligo analysis by computer-assisted grid (VACAG) in the combined Fr: CO2 laser with PRP and in the PRP only groups than other groups. These results were confirmed by mean improvement score by physician (MISP) and by VAS with no statistical difference between them. The combined Fr: CO2 laser with PRP group showed minimal side effects. Regardless of the modalities, better improvement was seen in the trunk than the face, extremities, and acral lesions with significant reduction in all regions. Face showed maximum response with combined Fr: CO2 laser with PRP. Trunk showed higher response with PRP. Upper limbs showed highest response with combined Fr: CO2 laser with PRP. Lower limbs showed the highest improvement with Fr: CO2 laser. Conclusion: According to our study, combined Fr: CO2 laser with PRP achieved superior repigmentation than intradermal (ID) PRP. However, Fr: CO2 alone showed poor improvement. Combined ablative Fr: CO2 laser and PRP therapy followed by sun exposure could be used effectively and safely to treat refractory NSV. Keywords: platelet-rich plasma, fractional carbon dioxide laser, melanoblasts, stem cells, nonsegmental vitiligo, refractory vitiligo, vitiligo, undifferentiated stem cell